Konishi OPE coefficient at the five loop order - Georgoudis, Alessandro [UNESP]; Gonçalves, Vasco [UNESP]; Pereira, Raul (Springer Nature, 2018)
We use the method of asymptotic expansions to study the OPE limit of a fourpoint function of protected operators in N= 4 SYM. We use a new method for evaluating the resulting propagator-type integrals and then extract the OPE coefficient with Konishi at the five loop order.
Keywords: Conformal Field Theory; Integrable Field Theories; Supersymmetric Gauge Theory